Disciplinary and Interdisciplinary Science Education Research - Zheng, Yonghe; Liu, Xiufeng; Wang, Lei.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Disciplinary and Interdisciplinary Science Education Research (DISER) promotes scholarship and best practices in education within and across science disciplines. DISER publishes original empirical, conceptual and policy studies reflecting the latest development in science education from disciplinary and interdisciplinary perspectives. DISER bridges the divide and facilitates dialogue between formal and informal, disciplinary and interdisciplinary, K-12 and post-secondary, as well as English-speaking and non-English speaking country science education. Disciplinary science education researchers and practitioners seeking interdisciplinary insights will find this journal to be particularly beneficial. DISER$1 (Bs scope is broad in both methodology and content. It is interested in research at all levels, including early childhood, primary, secondary, tertiary, workplace, and informal learning as they relate to science education. It publishes research in biology education, chemistry education, geology education, physics education, science education, and engineering education. Research can take various methodological approaches, including qualitative research designs (e.g., ethnography, narratives, case studies, historical/philosophical approaches, etc.), quantitative research designs (e.g., experimental and quasi-experimental designs, survey research, correlation study, measurement study, statistical research, etc.), and mixed methods. DISER also publishes position papers, critical reviews of literature, critique and comments and book reviews.s
Keywords: Education; Education